Implementasi Adaptive AI Pada Game Turn-Based RPG Dengan Menggunakan Metode Hierarchial Dynamic Scripting - Intishar Fadi Abdillah; Eriq Muh. Adams Jonemaro; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
There are many methods used by game developers in applying Artificial Intelligence (AI) into Non Playable Character (NPC) which aims to inhibit gamers in achieving their goals or mission. Scripting method is one of the most used method of game developers in designing AI in NPC because of its simple, flexible (easy to modify), and powerful process. Scripting method is a way to design behavior NPC through a combination of rules that are modeled with if-then sentences. The combination of these rules is explicitly written on source code or other external files (commonly referred to as hard coded) which is not possible to change the NPC behavior when the game has been released. This causes the NPC is often easily exploited by gamers who have understood the pattern of the NPC behavior. To overcome these problems, we need a method capable of producing an adaptive NPC behavior while still providing the nature of Scripting method that is simple, flexible, and powerful. Therefore, Hierarchial Dynamic Scripting method tries to answer the problem in this research. Hierarchial Dynamic Scripting method is an advanced development of the Dynamic Scripting method by adding Hierarchial Task Network architecture in it. The main principle of the Dynamic Scripting method is to assign specific weights to the set of rules and combine them into a dynamic script. Adaptive test results conducted in the game with the genre of Turn-Based Role Playing Game based on three parameters of the test of effectiveness, efficiency, and variation shows that the NPC using Hierarchial Dynamic Scripting method has a high effectiveness with the average fitness value of 0.73 and High efficiency by achieving an average turn-point value of 6 against all scenario tactics in this study. In addition, testing the value of break even point yields the best value of 0.5 to get a good level of NPC adaptability.